Further insights into the Fe(ii) reduction of 2-line ferrihydrite: a semi in situ and in situ TEM study. Issue 10 (30th September 2020) - Gomez, Mario Alberto; Jiang, Ruonan; Song, Miao; Li, Dongsheng; Lea, Alan Scott; Ma, Xu; Wang, Haibo; Yin, Xiuling; Wang, Shaofeng; Jia, Yongfeng
Abstract : The catalytic reduction of nano-crystalline 2-line ferrihydrite with Fe(ii )(aq) doesn't occur via direct pathways but rather through new intermediate steps. Abstract : The biotic or abiotic reduction of nano-crystalline 2-line ferrihydrite (2-line FH) into more thermodynamically stable phases such as lepidocrocite-LP, goethite-GT, magnetite-MG, and hematite-HT plays an important role in the geochemical cycling of elements and nutrients in aqueous systems. In our study, we employed the use of in situ liquid cell (LC) and semi in situ analysis in an environmental TEM to gain further insights at the micro/nano-scale into the reaction mechanisms by which Fe(ii )(aq) catalyzes 2-line FH. We visually observed for the first time the following intermediate steps: (1) formation of round and wire-shaped precursor nano-particles arising only from Fe(ii )(aq), (2) two distinct dissolution mechanisms for 2 line-FH ( i.e. reduction of size and density as well as breakage through smaller nano-particles), (3) lack of complete dissolution of 2-line FH ( i.e. "induction-period"), (4) an amorphous phase growth ("reactive-FH/labile Fe(iii ) phase") on 2 line-FH, (5) deposition of amorphous nano-particles on the surface of 2 line-FH and (6) assemblage of elongated crystalline lamellae to form tabular LP crystals. Furthermore, we observed phenomena consistent with the movement of adsorbate ions from solution onto the surface of a Fe(iii )-oxy/hydroxide crystal. Thus our work here reveals that the catalytic transformation of 2-line FH by Fe(ii )(aq) at the micro/nano scale doesn't simply occur via dissolution–reprecipitation or surface nucleation–solid state conversion mechanisms. Rather, as we demonstrate here, it is an intricate chemical process that goes through a series of intermediate steps not visible through conventional lab or synchrotron bulk techniques. However, such intermediate steps may affect the environmental fate, bioavailability, and transport of elements of such nano-particles in aqueous environments.